Exploring the structure of relative age effects research using citation network analysis - Froude, A. M.; Hancock, D. J.; McLaren, C. D.; Vierimaa, M.; Côté, J. (Journal of Sports Sciences, 2024)
Since the 1980s, research on relative age effects (RAEs) consistently shows that relatively older individuals are advantaged in sport and other contexts. With the recent proliferation of studies on RAEs, periodic knowledge synthesis becomes imperative. Our purpose was to conduct a cross-disciplinary citation network analysis of RAEs literature to enhance our knowledge of RAEs citation structures and the interconnectivity of RAEs studies. We analysed 484 RAEs articles found in Web of Science that were published before 2022. Descriptive results revealed a 12.6% annual growth rate for total RAEs articles published since 1980. The articles appeared in 151 journals, had 1,180 unique authors, and averaged 23.9 citations received. Three theoretical/review papers had the most substantial influence on the field. For the conceptual structure of the field, it was apparent that RAEs research focused mainly on sport performance, maturity, and competition. Regarding intellectual structure, three distinct clusters of articles were cited together, and 13 authorship clusters were detected with few between-cluster connections. The results describe a field with productivity but little interconnectivity among authors and papers. We offer insights into this trend and the role that influential authors/articles have in the field.